Prioritizing Consumer-Driven Features for Development: A Case Study of Teman Survei - Mutiara, Imelda; Herliana, Sri (Universitas Muhammadiyah Surakarta, 2023)
The research project aimed to identify the features most needed by customers of Teman Survei, an Indonesian startup in the property industry. The study employed a qualitative research approach to address which Teman Survei’s features are most needed by customers. Through thorough analysis and evaluation, the research findings revealed that the survey services were highly preferred by customers. This feature offered an immersive experience and allowed for comprehensive property condition evaluation without physical visits. The implications of the study highlighted the importance of aligning Teman Survei's services with customer expectations, enabling the company to optimize resources and avoid potential losses. By prioritizing the development of desired features based on customer needs, Teman Survei can enhance product-market fit, efficiency, and effectiveness. This research contributes to the advancement of the property industry in Indonesia and provides valuable insights for Teman Survei's business development.